1998
DOI: 10.1093/nar/26.4.954
|View full text |Cite
|
Sign up to set email alerts
|

Translational termination in Escherichia coli: three bases following the stop codon crosslink to release factor 2 and affect the decoding efficiency of UGA-containing signals

Abstract: The observations that the Escherichia coli release factor 2 (RF2) crosslinks with the base following the stop codon (+4 N), and that the identity of this base strongly influences the decoding efficiency of stop signals, stimulated us to determine whether there was a more extended termination signal for RF2 recognition. Analysis of the 3' contexts of the 1248 genes in the E.coli genome terminating with UGA showed a strong bias for U in the +4 position and a general bias for A and against C in most positions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 34 publications
5
44
0
2
Order By: Relevance
“…The actions of RNAs in release factor assays can be related to the structures of the proteins and the selected RNAs+ RF1, RF2, and eRF1 are RNA-binding proteins, and have in particular, affinity for termination codons+ Photoactivated termination codons containing 4-thiouridine (s 4 U; reviewed in Favre & Fourrey, 1995;Favre et al+, 1998) in the first position can be used to demonstrate this interaction+ In Escherichia coli ribosomes, s 4 UAA-containing 36-mer mRNA was shown to crosslink to the ribosomal RNA and with low efficiency to RF2 (Tate et al+, 1990)+ With s 4 UGAN instead of s 4 UAAN the yield of crosslinks between RF2 and s 4 UGAN increased (Brown & Tate, 1994)+ The identity of the fourth base in the stop signal also strongly affected the interaction with RF+ Further analysis demonstrated that three positions after the stop codon were able to crosslink to E. coli RF2, though the efficiency of crosslinking from the ϩ1 nucleotide was much higher than from ϩ4 and ϩ6 (Poole et al+, 1997(Poole et al+, , 1998)+ In addition, particular adjacent amino acid sequence changes within bacterial RF1 and RF2 alter the codon triplets translated as stop (Ito et al+, 2000), suggesting that bacterial RF is in contact with stop codon nucleotides+ Within eukaryotic ribosomes, the proximity of stop codons and human eRF1 has been similarly demonstrated using the photocrosslinking strategy (L+ Chavatte, L+ Frolova, L+ Kisselev, and A+ Favre, unpubl+)+ Ribosomal RNA is also close to RF+ A region of 16S ribosomal RNA has been found to crosslink to the RF+ For prokaryotic ribosomes genetic evidence also implicates ribosomal RNAs in translation termination (Arkov et al+, 1998)+ Moreover, the prokaryotic ribosomal A site where RF1/2 interacts can now be seen to be predominantly composed of ribosomal RNA (Ban et al+, 1999;Cate et al+, 1999)+ Release factors are therefore highly specialized proteins designed for an environment replete with RNAs+ Interference with any natural RNA site by a competing RNA would inhibit termination+ However, interference need not be specific+ General steric interference with ribosomal entry by a large polyanionic ligand like a tightly-bound RNA would presumably also disrupt termination+…”
Section: Structures Of the Reactantsmentioning
confidence: 99%
“…The actions of RNAs in release factor assays can be related to the structures of the proteins and the selected RNAs+ RF1, RF2, and eRF1 are RNA-binding proteins, and have in particular, affinity for termination codons+ Photoactivated termination codons containing 4-thiouridine (s 4 U; reviewed in Favre & Fourrey, 1995;Favre et al+, 1998) in the first position can be used to demonstrate this interaction+ In Escherichia coli ribosomes, s 4 UAA-containing 36-mer mRNA was shown to crosslink to the ribosomal RNA and with low efficiency to RF2 (Tate et al+, 1990)+ With s 4 UGAN instead of s 4 UAAN the yield of crosslinks between RF2 and s 4 UGAN increased (Brown & Tate, 1994)+ The identity of the fourth base in the stop signal also strongly affected the interaction with RF+ Further analysis demonstrated that three positions after the stop codon were able to crosslink to E. coli RF2, though the efficiency of crosslinking from the ϩ1 nucleotide was much higher than from ϩ4 and ϩ6 (Poole et al+, 1997(Poole et al+, , 1998)+ In addition, particular adjacent amino acid sequence changes within bacterial RF1 and RF2 alter the codon triplets translated as stop (Ito et al+, 2000), suggesting that bacterial RF is in contact with stop codon nucleotides+ Within eukaryotic ribosomes, the proximity of stop codons and human eRF1 has been similarly demonstrated using the photocrosslinking strategy (L+ Chavatte, L+ Frolova, L+ Kisselev, and A+ Favre, unpubl+)+ Ribosomal RNA is also close to RF+ A region of 16S ribosomal RNA has been found to crosslink to the RF+ For prokaryotic ribosomes genetic evidence also implicates ribosomal RNAs in translation termination (Arkov et al+, 1998)+ Moreover, the prokaryotic ribosomal A site where RF1/2 interacts can now be seen to be predominantly composed of ribosomal RNA (Ban et al+, 1999;Cate et al+, 1999)+ Release factors are therefore highly specialized proteins designed for an environment replete with RNAs+ Interference with any natural RNA site by a competing RNA would inhibit termination+ However, interference need not be specific+ General steric interference with ribosomal entry by a large polyanionic ligand like a tightly-bound RNA would presumably also disrupt termination+…”
Section: Structures Of the Reactantsmentioning
confidence: 99%
“…Although a direct role for the ribosome and rRNA in stop codon recognition has been proposed in the past, evidence now points to a direct recognition model for RF stop codon discrimination+ First, prokaryote RF2 can be directly UV crosslinked to the stop codon and downstream nucleotides in vitro, inferring the release factor is in intimate contact with the termination signal (Brown & Tate, 1994;Poole et al+, 1998)+ Second, overexpression of either prokaryote RF1 or eukaryote eRF1 acts to out-compete suppressor tRNA species for stop codon binding+ This so-called antisuppressor phenotype indicates both tRNAs and RFs are cognate species in direct competition for stop codon binding (Weiss et al+, 1984;Stansfield et al+, 1995a;Legoff et al+, 1997)+ Direct recognition models like these imply that RFs might act in a tRNA-like manner to discriminate between codons+ This idea was supported by the discovery that the structure of domain IV/V of elongation factor G complexed with GDP is very similar to that of a tRNA molecule when part of a ternary complex with EF-Tu and GTP, prompting the proposal that protein elongation factors might mimic tRNA molecules (Nissen et al+, 1995)+ On the basis of limited RF sequence similarity to EF-G, the concept of structural tRNA mimicry by the central domain of class I release factors was developed (Ito et al+, 1996)+ The recent solution of the crystal structure of eukaryote eRF1 has allowed a reappraisal of this model for eukaryote RFs, and it is now apparent that, although the central domain of eRF1 at least does not represent a tRNA-like structure (Song et al+, 2000), the Y-shaped eRF1 molecule does have both similar shape and overall dimensions to a tRNA+ The N-terminal domain 1 of eRF1 may represent a potential anticodonlike region, on the basis of its position relative to the peptidyl-release triggering GGQ motif (analogous to the tRNA CCA acceptor stem; Song et al+, 2000)+ Thus the eRF1-tRNA mimicry model is now supported by direct structural evidence, although it seems likely that the bacterial RFs may be structurally dissimilar to eRF1 because their predicted secondary structures are unalike+ It cannot, however, be ruled out that the bacterial RF overall shape may still mimic that of a tRNA+ Recently, the crystal structure of another ribosomal A siteinteracting protein, the bacterial ribosome recycling factor (RRF), has been solved, revealing it, too, has a tRNA-like shape, and strengthening the tRNA mimicry proposal (Selmer et al+, 1999)+ How then is stop codon recognition achieved by a tRNA-analog protein RF? In a recent study, mixed RF1/ RF2 domain hybrid proteins were constructed and screened for RF1 molecules with RF2-like stop codon specificity+ Tripeptide motifs were identified from the central D domain of both release factors that conferred codon specificity, with the first and third amino acids of this peptide discriminating the second and third purine bases of the stop codons (Ito et al+, 2000)+ These findings reinforce the proposal that bacterial RFs directly recognize the stop codon+ Eukaryote eRF1 from Tetrahymena, recently cloned (Karamyshev et al+, 1999), may exhibit natural altered stop codon recogn...…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the downstream nucleotides in the signal may be explained by the interactions these bases make with the RF since not only could we detect crosslinks from the +4, +5 and +6 positions of the mRNA to the RF but not beyond [42], but also bases in these +4 to +6 positions affected the efficiency of the signals when under competition from either non-cognate readthrough in the presence or absence of suppressor tRNAs, or from programmed frameshifting [39,41]. These results were also consistent with the accumulating bioinformatics predictions that indicated a bias beyond the +4 base.…”
Section: Is the Decoding Rf More Promiscuous Than A Trna In Its Contamentioning
confidence: 98%
“…The 3′ end of 23S rRNA, exposed at the surface of the ribosome near to the factor entry site to the active centre, was selected npg by SERF with both bacterial factors. The regions selected by RF1 uniquely included nucleotides from the GTPaseassociated centre (helix [42][43][44]. The GTPase-associated centre (including proteins L11 and L7/L12 stalk) is also at the side of the subunit where the RF enters the active centre of the ribosome.…”
Section: The Footprint Of the Bacterial Rf On The Ribosomementioning
confidence: 99%